Guideline for ethics review of clinical trials - Medical Ethics Society of China Anti-Cancer Association; Minghuang Hong; Zhao Yan (Holistic Integrative Oncology)
Abstract This article is the first ethical review technical guideline in the field of oncology in China, compiled by the Medical Ethics Society of China Anti-Cancer Association and jointly completed by 104 national ethics review experts in accordance with a series of Chinese laws and regulations. The document, taking into account the national conditions of China and from an integrated perspective, for the first time proposes a comprehensive ethical review of clinical research from five dimensions: "benefit-risk assessment, foster innovation, full process risk control, safeguard the right and interests of subjects by law, and Achieve gains in both survival duration and quality of life." The guideline emphasizes that benefit-risk assessment should be the primary task of ethical review in clinical trials, proposes trial designs that balance science and ethics to promote pharmaceutical innovation, and requires proactive tracking review to control risks in the trial process. It advocates for the collective protection of the rights and interests of research participants in accordance with the law and emphasizes that the dual benefits of research participants' survival time and quality of life are the goals and missions of ethical review. The publication of this article aims to provide ethical guidelines and operational technical guidance for the ethical review of clinical research in the field of oncology in China. The guideline, grounded in practicality, clarifies the composition and operational mechanisms of the ethics review committee and particularly emphasizes the full process review that pays close attention to and protects the rights and interests of research participants through informed consent, research protocol review, protection of vulnerable groups, benefit-risk assessment, privacy and security review, and tracking review. The document also provides detailed explanations of the operational procedures and key points for important aspects such as review focus and tracking review. To ensure that this guideline is in line with the latest research trends and more referential, the article also covers key issues such as the recruitment of research participants, ethical issues in medical device clinical research, and ethical review of investigator-initiated clinical research. Through a comprehensive analysis of these contents, the document provides comprehensive guidance and recommendations for ethical review in oncology clinical research, aiming to promote the ethical and scientific nature of clinical research and to ensure that the rights and interests of research participants are protected to the greatest extent possible.